Intelligent agent for electronic commerce using neural network approach / Yap Hui Sun - Yap, Hui Sun (2001)
This project is aims to developing a tool that able to collect relevant information from the World Wide Web and a tool that can be used to assists users in decision-making in the activities of e-commerce. It i been built by using the neural network of artificial intelligence approach. In more specific, the back propagation network was been used. This report contains seven chapters that uncovered the details of the project from the beginning through the end of the system evaluation and a conclusion chapter. These chapters and its contain are been arranged as the following: Chapter I - lntroduction, introducing the project various dimension, which includes the briefing of project definition, objective and scope. Chapter II - Literature Review, containing the finding on the areas related to the project, approach and algorithm used in the project and analysis of the existing system. Chapter - Methodology, justifying the method chosen for the system development, project planning that includes project schedule and system modules, procedure of the system, which are the functional and non-functional requirements,hardware and software used to develop the system. Chapter IV - System Design, describing the system now using graphic representation techniques and specifying in deep on both training and prediction module. It also describes on the database design and screen design of the system. Chapter V - System Implementation and Testing, describing the system implementation of the development environment, development of webs, Prediction Agent and ActiveX component. It also describes the testing of the system. Chapter VT - System Evaluation, presenting the evaluation of the system in term of its strengths as well as the limitations. Chapter VII - Conclusion, describing the problems encountered and solutions taken during the development of the system. Recommendations for future enhancements on the system and a conclusion that summarized of the project from the beginning of introduction through the end of system evaluation are included in this chapter.